Instagram Social Media as a Means of Self-Presentation for Celebrities in Pekanbaru City - Febrianti, Nabila; Indrawati, Indrawati (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Every interaction, every individual must present themselves as best as possible in front of others. The same applies to using Instagram social media. Apart from being used as a means of entertainment and finding information, Instagram can also be used as a means of self-presentation for its users. The self-presentation built by each individual on Instagram, especially by celebrities, is certainly diverse. However, in building self-presentation, there are differences between what is displayed on Instagram and the reality of the lives of these celebrities, so that it will cause the phenomenon of dramaturgy. This study aims to determine and analyze the self-presentation formed on Instagram. This research uses dramaturgy theory and also self-presentation theory. The subjects in this study are celebrities in Pekanbaru City who have at least 5000 followers and are still actively using Instagram. This research was conducted with a descriptive qualitative approach using purposive sampling technique. Data collection techniques in this study were obtained based on observation, interviews and documentation. The results of the research that the author managed to find and obtain were the self-presentation displayed by celebrities in terms of building personal branding, using captions, and also maintaining their existence on Instagram social media. In addition, in terms of dramaturgy, the author also found differences between the front stage and the back stage in terms of appearance and also the use of verbal language.